2014
DOI: 10.1111/jopr.12176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Experimental Coating to Improve the Zirconia‐Veneering Ceramic Bond Strength

Abstract: The experimental zirconia surface coating is a simple technique to increase the microroughness of the zirconia surface, and thereby improve the SBS to the veneering ceramic. It results in the least monoclinic content and produces no structural damage to the zirconia substructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 26 publications
4
30
0
Order By: Relevance
“…From these results, the surface of the C-NT group was characterized as a sharp, rough surface. Our R a results of the C-NT group are in agreement with those of a previous study [25]. An experimental glass slurry coated onto zirconia surfaces before sintering caused a significant increase in R a because the slurry contents adhered to the surfaces after sintering.…”
Section: Discussionsupporting
confidence: 92%
“…From these results, the surface of the C-NT group was characterized as a sharp, rough surface. Our R a results of the C-NT group are in agreement with those of a previous study [25]. An experimental glass slurry coated onto zirconia surfaces before sintering caused a significant increase in R a because the slurry contents adhered to the surfaces after sintering.…”
Section: Discussionsupporting
confidence: 92%
“…[5,8,10,[20][21][22][23] Dental laser application on zirconia is one of the surface treatment options evaluated previously to improve surface roughness and bond strength between zirconia and veneer ceramic. [8][9][10] The current study evaluated the effect of an industrial laser on zirconia surface. Results show that surface roughness was affected by laser irradiation (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] The studies that have evaluated laser application to improve the bond between the zirconia framework and the veneer ceramic have utilized only CO 2 , Nd:YAG, and Er: YAG lasers which are frequently used for dental applications. [8][9][10] But their use to enhance the bond strength between zirconia and the veneer ceramic did not show any significant increase when compared with the sandblasting method, which can be accepted as conventional method for surface roughening; improving the bond strength between zirconia and veneer ceramic can be achieved by increasing the surface roughness. In addition to these dental lasers, ytterbium laser is a quite powerful tool mainly used in the industry.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, some researchers have suggested that the framework design and thickness of the veneering porcelain must be considered [9,10]. Recently, alternative approaches including coating methods and plasma treatment for zirconia surfaces have been attempted for such studies [11,12]. …”
Section: Introductionmentioning
confidence: 99%